When learning organizations meet artificial intelligence: Reimagining cybersecurity governance for Algeria - Daghrir, Fathi; Zerrougui, Antar (The International tax journal, 2025)
What happens when we combine the timeless wisdom of organizational learning with the raw power of artificial intelligence to tackle national cybersecurity? This paper explores that question through a conceptual framework we developed specifically for Algeria. We started by examining Algeria’s digital landscape and found that while the country is rapidly modernizing, its cybersecurity approach tends to be reactive and fragmented. Our proposed solution is a three-layer architecture that moves beyond simple compliance, aiming instead to create a system that actually learns from its experiences. The framework draws inspiration from international standards but focuses on Algeria’s particular challenges with digital sovereignty. What we’re offering here is essentially the blueprint theoretical foundation for research that will, in future work, test whether this approach can work in practice.